Recent Advances for the Direct Introduction of the CF2Me Moiety - Carbonnel, Elodie; Poisson, Thomas; Jubault, Philippe; Pannecoucke, Xavier; Besset, Tatiana (Frontiers in Chemistry, 2019)
Fluorine-containing molecules are compounds of interest in materials as well as in pharmaceutical and agrochemical industries. Therefore, developments in that research field are tremendous and a special focus was dedicated to the design and the study of emergent fluorinated groups. In particular, the CF2Me residue is attractive as it could be used for example as a bioisostere of the methoxy group. Despite the clear asset that represents this fluorinated moiety and in complement to the traditional approaches used to construct the CF2Me residue from existing functional groups, the quest for direct methodologies for the 1,1-difluoroethylation reaction of molecules has triggered a strong interest from the scientific community. This Mini-review will focus on the recent advances towards the design of reagents and their applications for the direct 1,1-difluoroethylation of various classes of compounds.